2010
DOI: 10.1016/j.ijid.2009.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of hepatitis B virus surface antigen escape mutations and concomitantly nucleos(t)ide analog resistance mutations in Turkish patients with chronic hepatitis B

Abstract: The findings of this study show preexisting typical HBsAg escape and NUC resistance mutations are possible. The genetic arrangement of the HBV genome with polymerase and surface genes overlapping has substantial public health and diagnostic implications and relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
36
3
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 46 publications
11
36
3
9
Order By: Relevance
“…Several previous studies identified typical HBsAg amino acid substitutions are sP120T, sM133I, sS143L, sD144A/E, sG145R, sE164D, sW172*, and sW182* which is the most commonly occurring pattern (9,15,16). Vaccine escape/HBIg-selected escape mutants, sG145R and sP120T, in combination with LAM-associated resistance mutations, are often seen in HBV mono-infected patients after LAM or HBIg treatment (31).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Several previous studies identified typical HBsAg amino acid substitutions are sP120T, sM133I, sS143L, sD144A/E, sG145R, sE164D, sW172*, and sW182* which is the most commonly occurring pattern (9,15,16). Vaccine escape/HBIg-selected escape mutants, sG145R and sP120T, in combination with LAM-associated resistance mutations, are often seen in HBV mono-infected patients after LAM or HBIg treatment (31).…”
Section: Discussionmentioning
confidence: 96%
“…Although most patients were identified to be hepatitis B e-antibody-positive asymptomatic carriers, they were found to be older in age with low hepatitis B e-antigen positivity, low alanine aminotransferase level, and low HBV DNA levels (Table 1). Our previous reports established that the frequencies of naturally occurring primary and compensatory mutations are very high in treatmentnaive HD patients when compared to treatment-naive CHB patients with normal renal function (15,23). However, clinical manifestation and the number of viral genomic substitutions in HBV carriers may be influenced by aging under long-term pressure from the host immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAM ve LdT kullanımının yaygın ya da zorunlu olduğu popülasyonlarda (ülke-mizde bir süre öncesine kadar geçerli olan SUT'a göre KHB'li hastalarda HBV DNA düzeyi <10 7 İÜ/ml ise NA tedavisi yalnız LAM ya da LdT ile başlatılabilmekteydi) primer ve kompansatuar ilaç direnci mutasyonları sıklıkla saptanmaktadır (153)(154)(155)(156). KHB'li hastaların NA tedavilerinde ortaya çıkabilen primer ve kompansatuar ilaç direnci mutasyonları ve S geninde yol açtıkları aminoasid değişiklikleri Tablo 5'te görülmektedir.…”
Section: Nükleoz(t)id Analoglarına Karşı Viral Direnç Ve Direncin İzlemiunclassified
“…HBV pol geninde NA hedef bölgesinde meydana gelen kompansatuar mutasyonlar, KHB'li hastaların tedavilerinde gereksiz ya da hatalı ilaç değişiklikleri yapılmasına yol açmaktadır. Hem NA naif hem de LAM ve/veya ADV tedavisi alan KHB hastalarında rtQ215H/Q/P/S kompansatuar mutasyonları sık saptanmaktadır (153)(154)(155)(156)(157). Bu nedenle NA tedavilerinde yapılacak ilaç değişikliklerinde ve rasyonel bir NA yönetiminde HBV ilaç direnci analizleri yapılması önemlidir.…”
Section: Nükleoz(t)id Analoglarına Karşı Viral Direnç Ve Direncin İzlemiunclassified